INOVASI MEDIA KARTU YOGA PRETZEL GAMES TERINTEGRASI SOCIAL EMOTIONAL LEARNING PADA PEMBELAJARAN SEKOLAH DASAR - Agustini, Luh Tia; Putu Nanci Riastini; Ni Made Dainivitri Sinta Sari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The low level of social and emotional skills among elementary school students remains a problem in learning practices, as evidenced by their lack of self-confidence, interaction skills, and ability to manage emotions. This study aims to produce Yoga Pretzel Games media integrated with Social Emotional Learning (SEL) based on content validity and response validity. This study uses the ADDIE model with a research and development type of research. The research subjects included subject matter experts, media experts, elementary school teachers, and elementary school students. The results of this study were then analyzed using quantitative techniques. The validity test results obtained a very high category from subject matter experts with a score of 1, and the validity test by learning media experts obtained a score of 1. The feasibility of the media was also assessed from the teachers' responses, which obtained a score of 100%, and the student response test obtained a score of 98%. Based on these results, it was concluded that the developed media was feasible and practical for improving students' social-emotional skills and creating a pleasant learning atmosphere. The implications of the study indicate that the integration of card-based yoga can be an alternative holistic learning media to support the implementation of SEL in elementary schools.